Water immersion behavior of CNF/GNP reinforced green epoxy hybrid nanocomposites - Yusuf, J.; Sapuan, S.M.; Rashid, Umer; Ilyas, R.A.; Hassan, M.R. (Elsevier B.V., 2025)
Environmental challenges have prompted the development of sustainable materials such as nanocomposites. However, these composites exhibit inadequate water resistance, leading to suboptimal performance. This study investigates the impact of water absorption on the properties of green epoxy nanocomposites reinforced with low loading of cellulose nanofibrils (CNF) and graphene nanoplatelets (GNP) at (0.1, 0.25, and 0.5) wt%. After 15 days of water immersion, contact angle tests showed that CNF increased hydrophilicity 80.26°, while GNP improved water resistance 90.04°. The presence of nanoparticles was confirmed by XRD and Raman spectra. Micrographs from FESEM confirmed the role of CNF in making nanocomposite hydrophilic due to water molecule penetration through capillary flow due to hydrolytic breakdown. Mechanical tests indicated a 46.6 % increase in hardness for water-absorbed hybrid nanocomposites, with GNP enhancing impact resistance, tensile strength ranging from 400 to 600 MPa and flexural strength between 600 and 800 MPa. Thermally, the composites offer conductivity values of 10–30 W/m·K, supporting efficient heat dissipation, and maintain structural integrity at temperatures up to 300 °C due to the synergistic effects of CNF and GNP. The GNP enhances interfacial bonding with the epoxy matrix through π–π stacking and van der Waals forces. Its high aspect ratio and 2D structure improve stress transfer, load distribution, and crack resistance. Additionally, GNP forms continuous thermal pathways, boosting thermal conductivity and heat dissipation. This study emphasizes that filler dispersion and component interaction play vital roles in defining density performance and water absorption and highlights the role of filler type and dispersion in controlling moisture behavior, offering the potential for moisture-resistant composites in electronics applications.